2015
DOI: 10.1007/s11356-015-5816-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of arsenic species with tropical river aquatic humic substances enriched with aluminum and iron

Abstract: The mobility and bioavailability of arsenic (As) are strongly controlled by adsorption/precipitation processes involving metal oxides. However, the organic matter present in the environment, in combination with these oxides, can also play an important role in the cycle of arsenic. This work concerns the interaction between As and two samples of aquatic humic substances (AHS) from tropical rivers. The AHS were extracted as proposed by IHSS, and were characterized by (13)C NMR. The experiments were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Gontijo et al (2016) studied the bioavailability of arsenic in Brazilian rivers, showing that a considerable part of As was inserted in the labile fraction, and can therefore be attributed to its bioavailability. In the same way, studies proposed by Oliveira et al (2015) reported no interaction between HS and As (III) in natura or enriched with aluminum, taking into account NOM environmental relevant. Jones and Huang (2003) showed an apparent non-linear toxicity response for organic pesticides composed of arsenic after interacting with humic substances at varying concentrations, suggesting a complex relationship where several mechanisms for toxicity reduction may be operative.…”
Section: Complexation Experimentssupporting
confidence: 54%
See 1 more Smart Citation
“…Gontijo et al (2016) studied the bioavailability of arsenic in Brazilian rivers, showing that a considerable part of As was inserted in the labile fraction, and can therefore be attributed to its bioavailability. In the same way, studies proposed by Oliveira et al (2015) reported no interaction between HS and As (III) in natura or enriched with aluminum, taking into account NOM environmental relevant. Jones and Huang (2003) showed an apparent non-linear toxicity response for organic pesticides composed of arsenic after interacting with humic substances at varying concentrations, suggesting a complex relationship where several mechanisms for toxicity reduction may be operative.…”
Section: Complexation Experimentssupporting
confidence: 54%
“…Heavy metals were predominantly bound to highmolecular-mass colloids bigger than 10 kDa (Burba et al, 1998). Oliveira et al (2015) states that environmental anionic or neutral species and more than one mechanisms can contribute to formation of As(III)-AHS complexes. The same authors, after studying AHS enriched with Fe and Al by fluorescence spectra, observed changes in structures of fulvic and humic acids.…”
Section: Tablementioning
confidence: 99%
“…7), which results in repulsion forces between As and negatively charged AHS at high pH. However, the presence of dissolved Fe and Al, as mentioned in Barbiero et al (2016), leads to the formation of ternary complexes (As-Fe/Al-AHS) (Oliveira et al, 2016). This behavior could be at the origin of the results of the ANCOVA, emphasizing that the evaporation, but also the DOC content and the origin of the samples coming from the organic horizons have a significant influence on dissolved As (Table 3) (Ghosh et al, 2015;Mariot et al, 2007) .…”
Section: Discussionmentioning
confidence: 99%
“…The exemplary excitation-emission matrices (EEM) of FAs at different pH are shown in Figure 1. The maxima of fluorescence intensities (FI) for the A-peak were located at ex/em: ~320 nm/~440 nm and were attributed to the humic substances of higher molecular weight [41] and Vis fulvic-like systems [42]. Fluorescent regions, located at longer excitation wavelengths, can be also related to the greater number of conjugated aromatic π-electron structures with electron withdrawing functional groups such as C=O [43,44].…”
Section: Fluorescence Properties Of Fasmentioning
confidence: 99%
“…Fluorescent regions, located at longer excitation wavelengths, can be also related to the greater number of conjugated aromatic π-electron structures with electron withdrawing functional groups such as C=O [43,44]. The maximum of the A-peak was slightly shifted (5-10 nm) toward the The maxima of fluorescence intensities (FI) for the A-peak were located at ex/em:~320 nm/~440 nm and were attributed to the humic substances of higher molecular weight [41] and Vis fulvic-like systems [42]. Fluorescent regions, located at longer excitation wavelengths, can be also related to the greater number of conjugated aromatic π-electron structures with electron withdrawing functional groups such as C=O [43,44].…”
Section: Fluorescence Properties Of Fasmentioning
confidence: 99%